Membrane-Coated Biomimetic Nanoparticles: A State-of-the-Art Multifunctional Weapon for Tumor Immunotherapy - Yuanyuan Zhang; Xinyi Zhang; Haitao Li; Jianyong Liu; Wei Wei; Jie Gao (Membranes, 2022)
The advent of immunotherapy, which improves the immune system’s ability to attack and eliminate tumors, has brought new hope for tumor treatment. However, immunotherapy regimens have seen satisfactory results in only some patients. The development of nanotechnology has remarkably improved the effectiveness of tumor immunotherapy, but its application is limited by its passive immune clearance, poor biocompatibility, systemic immunotoxicity, etc. Therefore, membrane-coated biomimetic nanoparticles have been developed by functional, targeting, and biocompatible cell membrane coating technology. Membrane-coated nanoparticles have the advantages of homologous targeting, prolonged circulation, and the avoidance of immune responses, thus remarkably improving the therapeutic efficacy of tumor immunotherapy. Herein, this review explores the recent advances and future perspectives of cell membrane-coated nanoparticles for tumor immunotherapy.